Light inhibits the production of alternariol and alternariol monomethyl ether in Alternaria alternata. - Söderhäll, K (1978)
Alternaria alternata (Fr.) Keissler, grown in drop culture, produced alternariol and alternariol monomethyl ether in late growth phase. Production was almost completely inhibited when the fungal cultures were exposed to white light (180 W/m2), although mycelial dry weight was not significantly affected. The fungus was most sensitive to light during the exponential growth phase. Twelve hours of light exposure was sufficient to decrease significantly the production of the secondary metabolites. In light the fungus produced a red-brown pigment of unknown nature.